Sondheim and Me Recalling a Genius. - Salsini, Paul (Bancroft Press, 2022)
Paul Salsini's memoir details his unique relationship with American musical composer Stephen Sondheim throughout his years as the founder and editor of The Sondheim Review, the only publication devoted solely to Sondheim's work during his lifetime.